THE VIKING ROAD TO BYZANTIUM. - Davidson, H. R. Ellis (Hilda Roderick Ellis), 1914-2006. ([S.l.])
1 online resource.
Keywords: The Viking Road to Byzantium (1976) is a major study of the Vikings who travelled east, based on the evidence of written sources and archaeology. Clues to the movements of the eastern Vikings may be found not only in Icelandic skaldic verse and runic inscriptions on memorial stones, but in such unexpected places as a Romanian chalk quarry near the Black Sea, among the carved stones of ancient Thrace and in Constantinople itself, the Miklagard of northern literature.